Effects of Age and Sex on the Single-Dose Pharmacokinetics and Pharmacodynamics of Apixaban - Frost, Charles E.; Song, Yan; Shenker, Andrew; Wang, Jessie; Barrett, Yu Chen; Schuster, Alan; Harris, Stuart I.; LaCreta, Frank (Clinical pharmacokinetics, 2015)
Background and Objectives The effects of age and sex on apixaban pharmacokinetics and pharmacodynamics were studied. Methods This was an open-label, single-dose, 2 × 2 factorial study. Healthy young (aged 18–40 years) and elderly (aged ≥65 years) male and female subjects received a single oral 20 mg dose of apixaban. Blood and urine samples were collected for pharmacokinetic and pharmacodynamic (blood only) analyses. Subjects were monitored for adverse events throughout the study. Results Seventy-nine subjects were enrolled into four groups: young males ( n = 20), elderly males ( n = 20), young females ( n = 20) and elderly females ( n = 19). Age did not affect the maximum observed plasma concentration ( C max ). The mean area under the concentration–time curve from time zero extrapolated to infinite time (AUC ∞ ) was 32 % greater in elderly subjects than in young subjects. The mean C max and AUC ∞ values were 18 and 15 % higher, respectively, in females than in males. The time course of the mean international normalized ratio (INR), modified prothrombin time (mPT) and anti-Xa activity tracked the apixaban concentration–time curve. All three pharmacodynamic measures exhibited a positive linear correlation with the plasma apixaban concentration. Differences in the mean INR, mPT and anti-Xa activity between age and sex groups were small (<15 % at the maximum mean values) and were generally related to pharmacokinetic differences. However, anti-Xa activity demonstrated less variability than the INR or mPT, and may have utility as a bioassay for apixaban. Apixaban was well tolerated, with no serious adverse events. Conclusion There were no clinically meaningful age- or sex-related differences in the pharmacokinetics and pharmacodynamics of apixaban that would require dose modification on the basis of age or sex alone.